Pemahaman Mahasiswa Akuntansi terhadap Konsep Dasar Akuntansi - Dewi, Novia Citra; Misneli; Aryuna, Wemi; Regita (SAFE-Network, 2025)
This study analyzes the level of understanding of final-year accounting students at UIN Imam Bonjol Padang regarding basic accounting concepts, considering gender and educational background. The objectives are to measure the understanding of basic accounting elements (assets, liabilities, equity, revenue, expenses, accounting cycle), identify differences based on gender and educational background, and identify obstacles and solutions. A descriptive quantitative approach was used through a questionnaire survey of 103 active students of the Accounting Study Program at UIN Imam Bonjol Padang. Data were analyzed using the Mann-Whitney Test for gender and the Kruskal-Wallis Test for educational background. The results show that students' overall understanding is good (average 81%). The accounting cycle has the highest understanding (89%), while liabilities have the lowest (70%). There is a significant difference in understanding based on gender (p=0.014), where women are better than men. A significant difference was also found based on educational background (p=0.002), with graduates of Accounting Vocational Schools showing the best understanding. Obstacles include difficulty understanding terms, distinguishing debits/credits, lack of focus, minimal practicums, and infrequent lecturers. Suggested solutions are increasing practicums and adding accounting books to the library.